Interrupted borrowing hydrogen strategy enabled aminomethylation and direct cross-dehydrogenative coupling strategy enabled dicarbonylation reactions of imidazo[1,5-a]pyridines - Mahajan, Shivangani; Bag, Debojyoti; Kour, Harpreet; Sawant, Sanghapal D. (Chemical Communications, 2025)
Herein, we disclose the development of novel aminomethylation and dicarbonylation reactions of imidazo[1,5-a]pyridines. The developed aminomethylation strategy involves a Pd-catalyzed interrupted borrowing hydrogen strategy by utilizing MeOH as the methylene source. A wide variety of imidazo[1,5-a]pyridines and secondary amines were explored for the developed strategy. The established imidazo[1,5-a]pyridine dicarbonylation strategy involves a catalyst/additive-free direct cross-dehydrogenative coupling reaction between imidazo[1,5-a]pyridines and 2-oxoaldehydes.